INDIGENOUS KNOWLEDGE MANAGEMENT FOR SUSTAINABLE DEVELOPMENT IN NIGERIA: A PROTOTYPE FOR ADOPTION (NAU Journal of Library and Information Science, 2025)
This paper discusses indigenous knowledge management for sustainable development in Nigeria, using Nonaka‟s Socialization, Externalization, Combination, and Internalization (SECI) model as a prototype for adoption. Indigenous knowledge (IK) popularly known as traditional knowledge has its numerous benefits, with a high capability of contributing positively to sustainable development in Nigeria if it is rightly utilized and applied to diverse situations. This paper discusses the categories of IK, benefits of IK, and knowledge management procedures in managing IK, among others. It also identified some challenges limiting the use and application of IK such as low recognition of IK, lack of IK policy, and hi unwillingness on the part of the custodians to share IK among others. As concluded in this paper, Nonaka‟s SECI model should be adopted in promoting a viable and feasible solution to the numerous problems affecting the proper management of IK and scientific knowledge (SK) in Nigeria. The adoption of this model would help to improve the capturing, sharing, and utilization of indigenous and scientific knowledge in local and non-local communities in Nigeria. Also, this model will also help in bringing out striking areas of differences and similarities in the application of IK and SK; thereby promoting sustainable development rather than segregating one as inferior to the other.
Keywords: Indigenous knowledge, Sustainable development, knowledge management, Model, Adoption